Comparison of behind-the-ear vs. off-the-ear speech processors in cochlear implants: A systematic review and narrative synthesis - Muhammed Ayas; Jameel Muzaffar; Veronica Phillips; Manohar Bance (PLoS ONE, 2025)
Background Cochlear implants (CI) with off-the-ear (OTE) and behind-the-ear (BTE) speech processors differ in user experience and audiological performance, impacting speech perception, comfort, and satisfaction. Objectives This systematic review explores audiological outcomes (speech perception in quiet and noise) and non-audiological factors (device handling, comfort, cosmetics, overall satisfaction) of OTE and BTE speech processors in CI recipients. Methods We conducted a systematic review following PRISMA-S guidelines, examining Medline, Embase, Cochrane Library, Scopus, and ProQuest Dissertations and Theses. Data encompassed recipient characteristics, processor usage, speech perception, and non-audiological factors. Studies were assessed for quality and risk of bias by using Newcastle-Ottawa Scale (NOS). Results Nine studies involving 204 CI recipients, with a mean age of 49.01 years and 6.62 years of processor use, were included. Audiological results indicated comparable performance in quiet environments, with a slight preference for OTE in noisy conditions. For non-audiological factors, OTE processors excelled in comfort, handling, and aesthetics, leading to higher satisfaction. More data on medical complications and long-term implications is needed. Conclusion OTE processors may offer comparable performance to BTE processors in certain conditions, though not universally across all audiological outcomes. Interpretation depends on settings, processor generation, and testing paradigms. However, non-audiological factors might favour OTE. Understanding current literature may guide professionals in selecting suitable processors for CI recipients.